Properties of Fresh and Hardened Concrete Containing Supplementary Cementitious Materials State-of-the-Art Report of the RILEM Technical Committee 238-SCM, Working Group 4 - De Belie, Nele.; Soutsos, Marios .; Gruyaert, Elke.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume represents the current knowledge on the effect of SCMs (slag, fly ash, silica fume, limestone powder, metakaolin, natural pozzolans, rice husk ash, special SCMs, ternary blends) on the properties of fresh and hardened concrete (e.g. early strength development, workability, shrinkage) and curing requirements. Other topics treated in the book are postblending vs preblending, implications of SCM variability, interaction between SCM and commonly used admixtures (e.g. superplasticizers, air entrainers).
Preface -- Introduction -- Chapter 1. Ground Granulated Blast-furnace Slag, by Winnie Matthes, Anya Vollpracht, Yury Villagrán, Siham Kamali-Bernard, Doug Hooton, Elke Gruyaert, Marios Soutsos, Nele De Belie -- Chapter 2. Fly Ash, by Kosmas Sideris, Harald Justnes, Marios Soutsos and Tongbo Sui -- Chapter 3. Silica Fume, by Robert C. Lewis -- Chapter 4. Limestone Powder, by Luc Courard, Duncan Herfort, Yury Villagrán -- Chapter 5. Metakaolin, by F. Wang, K. Kovler, J.L. Provis, A. Buchwald, M. Cyr, C. Patapy, S. Kamali-Bernard, L. Courard, and K. Sideris -- Chapter 6. Natural Pozzolans, by Christos Dedeloudis, Monika Zervaki, Kosmas Sideris, Maria Juenger, Natalia Alderete, Siham Kamali-Bernard, Yury Villagrán, Ruben Snellings -- Chapter 7. Alternative Supplementary Cementitious Materials, by Konstantin Sobolev, Marina Kozhukhova, Kosmas Sideris, Esperanza Menéndez, Manu Santhanam -- Chapter 8. Rice Husk Ash, by Guang Ye, Hao Huang and Nguyen Van Tuan -- Chapter 9. Ternary Blends, by R. Doug Hooton, Semion Zhutovsky, Siham Kamali-Bernard.
Keywords: Building materials; Materials -- Analysis; Mechanics, Applied; Solids; Materials; Building Materials; Characterization and Analytical Technique; Solid Mechanics; Materials Engineering